Disordered stacked ultrathin nanosheet BiOCl photocatalyst and preparation method thereof
By reducing the amount and molecular weight of chitosan and combining with citric acid inducers, the disorderly stacked ultra-thin nanosheet-like BiOCl photocatalyst is prepared, which solves the problem of insufficient response of traditional BiOCl photocatalysts to visible light, and achieves higher photocatalytic activity and wastewater degradation efficiency.
Patent Information
- Application Number
- CN202510084023.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional BiOCl photocatalysts have weak responses to visible light and have low utilization of sunlight, resulting in their photocatalytic activity not being fully exerted.
By reducing the amount of chitosan and reducing its molecular weight, combined with citric acid as an auxiliary structure inducer, a disorderly stacked ultra-thin nanosheet-like BiOCl photocatalyst is prepared, which significantly reduces the nanosheet thickness, increases the specific surface area and oxygen vacancy content, and reduces the band gap energy.
The specific activity of BiOCl photocatalyst is improved, the optical wave response range is broadened, and its application efficiency in organic wastewater degradation is enhanced.
Smart Images

Figure CN119909706A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wastewater treatment, and in particular to a preparation method and a catalyst of a BiOCl photocatalyst for degrading organic matter in wastewater. Background Art
[0002] Antibiotics are widely used to treat infections, but due to their incomplete metabolism in humans and animals, 30%-90% of the unmetabolized part is discharged into the environment through wastewater. Tetracycline is a broad-spectrum antibiotic with strong antibacterial effects, but due to its hydrophilicity and long half-life, it tends to persist in aquatic environments, promote the emergence of antibiotic-resistant bacteria, and affect microbial communities. Therefore, controlling the emission and residue of these pollutants is crucial to protecting water resources and public health. Photocatalytic degradation is a process that uses ultraviolet light, visible light or infrared light to convert environmental pollutants into benign or less harmful products on a solid surface. Photocatalytic materials with high catalytic activity are the core of photocatalytic degradation technology. Semiconductor photocatalytic technology can effectively convert light energy into chemical energy, has strong oxidation ability, and can effectively oxidize and degrade difficult-to-degrade pollutants. Most photocatalysts are non-toxic, stable, and have mild photocatalytic reaction conditions, so they have good development prospects.
[0003] BiOCl-based materials have [Bi2O2] 2+BiOCl has attracted widespread attention due to its special structure of interlaced C1 and C2 layers. The special layered structure of BiOCl itself and its characteristics of non-toxicity, high abundance of component elements, low preparation cost, and stable chemical and optical properties make BiOCl an important material in the field of photocatalytic research. However, the shortcomings of BiOCl prepared by traditional methods, such as weak response to visible light and low utilization rate of sunlight, limit its photocatalytic application. In order to improve the response intensity of BiOCl to visible light and increase the utilization rate of sunlight, researchers considered improving the preparation method of BiOCl. For example, Chinese patent application CN110813325A discloses a method for preparing a BiOCl hollow microsphere photocatalyst, which uses a large amount of chitosan with a molecular weight of 5-20 kDa as a structural inducer, which is dissolved in a mixed acid solution, and then added to a bismuth salt solution at a relatively low temperature (5-20°C) and stirred to form a colloidal state, which is used to wrap the bismuth salt to form microspheres, and then slowly add a chloride solution to the system under stirring conditions, and after constant temperature stirring at 5°C-20°C, transfer to a high-pressure reactor for homogeneous reaction at 50-300°C and 3-30rpm for 6-24h, and centrifuge to obtain the product, which is a BiOCl hollow microsphere photocatalyst. The product morphology is shown in the attached figure, and has a typical hollow microsphere structure morphology. Subsequent studies have found that this morphology of the BiOCl photocatalyst is a regular shape formed by a number of closely stacked nanosheets, with a BET surface area of 23.6m 2 / g, its structure is still relatively dense, and the catalytic active sites of many nanosheets are covered by adjacent nanosheets, which results in the catalytic activity of the catalyst not being fully exerted, and the catalytic specific activity needs to be further improved. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a method for preparing a disorderly stacked ultrathin nanosheet BiOCl photocatalyst. The method reduces the amount of chitosan used and the molecular weight of chitosan to prevent it from being in a colloidal state, and uses citric acid as an auxiliary structure inducer to prepare a disorderly stacked nanosheet BiOCl photocatalyst. The photocatalyst not only has ultrathin nanosheets but also has a looser structure, thereby exposing more catalytic active sites, increasing the specific surface area of the catalyst, and reducing the band gap energy and broadening the light wave response range, thereby effectively improving the specific activity of the BiOCl photocatalyst, and further promoting the application of the BiOCl photocatalyst in the degradation of organic wastewater.
[0006] (II) Technical solution
[0007] The present invention provides a method for preparing a disorderly stacked ultrathin nanosheet BiOCl photocatalyst, which comprises the following steps:
[0008] S1, dispersing chitosan with a molecular weight of 1000-4000Da into water, stirring to obtain a 1.6-5.0g / L chitosan aqueous dispersion, adding a water-soluble bismuth salt and citric acid thereto, wherein the final concentration of the bismuth salt is 0.03-0.05mol / L, and the final concentration of the citric acid is 1.5-2.0g / L, stirring to fully dissolve the chitosan, and obtaining a first solution;
[0009] S2, providing a chloride salt aqueous solution with a concentration of 0.3-0.5 mol / L, wherein the molar amount of bismuth salt in the first solution and the molar amount of chloride ions in the chloride salt aqueous solution are 1:1-1.2, and the chloride salt aqueous solution is uniformly added to the first solution over a period of 5-10 min, and stirred to form a precursor solution;
[0010] S3, transferring the precursor solution into a high pressure reactor and sealing it, and reacting it at 150-170°C for 6-12 hours;
[0011] S4. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The solid is washed with ethanol and deionized water and dried to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
[0012] According to a preferred embodiment of the present invention, in S1, the molecular weight of chitosan is 2000-3000Da; and 50-150g chitosan is used for every 1mol of bismuth salt, preferably 100g chitosan.
[0013] According to a preferred embodiment of the present invention, in S1, the concentration of the chitosan aqueous dispersion is 3.33 g / L; the final concentration of the bismuth salt is 0.033 mol / L, and the final concentration of the citric acid is 1.67 g / L.
[0014] According to a preferred embodiment of the present invention, in S1, the water-soluble bismuth salt is at least one of bismuth nitrate, bismuth acetate, bismuth citrate and any one of the aforementioned bismuth salt hydrates.
[0015] According to a preferred embodiment of the present invention, in S2, the chloride salt refers to one of potassium chloride, sodium chloride and hexadecyl ammonium chloride; preferably potassium chloride.
[0016] According to a preferred embodiment of the present invention, the operating temperature in S1 and S2 is 25-50°C, preferably 30-35°C.
[0017] According to a preferred embodiment of the present invention, in S3, the reaction is stopped at 160° C. for 10-12 hours.
[0018] According to a preferred embodiment of the present invention, in S4, after the reaction is completed, the mixture is cooled to room temperature and centrifuged, the solid is washed with ethanol and deionized water for more than two times, and kept at 50°C-80°C for 6-10 hours to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
[0019] In a second aspect, the present invention provides a disorderly stacked ultrathin nanosheet BiOCl photocatalyst, which is prepared by the preparation method of any of the above embodiments.
[0020] Preferably, the BiOCl nanosheets in the nanosheet BiOCl photocatalyst have a thickness of 15-35 nm, a band gap energy of 2.95 eV, a light absorption edge of 389 nm, and a BET surface area of 25.0871 cm 2 / g; for tetracycline with an initial concentration of 10 mg / L, the degradation rate of tetracycline by 0.05g catalyst sample reached 88.36% within 60min.
[0021] In contrast, the thickness of each BiOCl nanosheet without chitosan induction is about 40-60 nm, the band gap energy is 3.13 eV, and the BET surface area is 9.546 cm 2 / g; for tetracycline with an initial concentration of 10 mg / L, the degradation rate of 0.05g catalyst sample was less than 60% in 60min.
[0022] (III) Beneficial effects
[0023] The preparation method of the present invention has the following technical effects:
[0024] (1) Chitosan was used as a structural inducer to change the crystal growth direction of bismuth oxychloride, significantly reducing the thickness of BiOCl nanosheets prepared by traditional methods, enhancing their light absorption capacity for visible light, increasing the specific surface area and oxygen vacancy content, and thus enhancing their photocatalytic degradation performance of organic pollutants. The infrared spectrum of the product confirmed that chitosan, which was used as a structural inducer in the preparation process, had decomposed after undergoing a hydrothermal reaction.
[0025] (2) The present invention utilizes a low molecular weight and low concentration chitosan dispersion and citric acid as dual structure inducers to prepare a BiOCl photocatalyst having ultrathin nanosheets and a looser stacking structure, which can expose more active sites of the nanosheets, increase the specific surface area of the catalyst, and reduce the band gap energy. The lower band gap energy enables it to be excited by most visible light, and the strongly oxidized photogenerated holes and photogenerated electrons on the surface of the photocatalyst are efficiently separated and can be quickly transferred to the surface to participate in free radical redox reactions, thereby broadening the light wave response range and visible light utilization efficiency of BiOCl, improving the specific activity of the photocatalyst, and further promoting the application of BiOCl photocatalyst in the degradation of organic wastewater.
[0026] PL spectrum was used to test the photogenerated carrier recombination process of the photocatalytic material after receiving photons. The results showed that the photocatalyst prepared by the present invention can reduce the recombination rate of photogenerated electron pairs. Nitrogen adsorption experiments confirmed that the BET area of the photocatalyst prepared by the present invention is 2.63 times that of BiOCl without chitosan induction (using only citric acid as structural induction). This shows that the preparation of BiOCl by the dual inducer of the present invention helps to increase the specific surface area and pore size of the material, provide more active sites for photochemical reactions, and help to increase the adsorption of pollutants, thereby improving the photocatalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 1 and 2 are XRD diagrams of the photocatalyst BiOCl of Example 1, Examples 4-5 and Comparative Example 1 of the present invention.
[0028] Figure 2 The thickness of the nanosheets of the photocatalyst BiOCl in Example 1 of the present invention (b) and the thickness of the nanosheets of the photocatalyst BiOCl without chitosan induction (a).
[0029] Figure 3 This is an infrared spectra of the photocatalyst BiOCl of Example 1 of the present invention and the photocatalyst BiOCl without chitosan induction.
[0030] Figure 4 It is a UV-visible diffuse reflectance spectra of the photocatalyst BiOCl of Example 1 of the present invention and the photocatalyst BiOCl without chitosan induction.
[0031] Figure 5 PL spectra of the photocatalyst BiOCl of Example 1 of the present invention and the photocatalyst BiOCl without chitosan induction.
[0032] Figure 6 1 and 2 are nitrogen adsorption curves of the photocatalyst BiOCl according to Example 1 of the present invention and the photocatalyst BiOCl without chitosan induction.
[0033] Figure 7 This is a photo of the colloidal state of chitosan during the preparation of BiOCl hollow microsphere photocatalyst in Comparative Example 2.
[0034] Figure 8 This is the SEM image of the BiOCl hollow microsphere photocatalyst of Comparative Example 2 at a scale of 2 μm.
[0035] Fig. 9 The degradation curves of the photocatalyst BiOCl of Examples 1-5 of the present invention and Comparative Examples 1-2 to tetracycline at an initial concentration of 10 mg / L under irradiation with a 300W xenon lamp are shown. DETAILED DESCRIPTION
[0036] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0037] Example 1
[0038] This embodiment prepares a method for preparing a disorderly stacked ultra-thin nanosheet BiOCl photocatalyst, and the steps are as follows:
[0039] (1) Disperse 0.2 g of chitosan with a molecular weight of 2000 Da into 60 mL of water and stir for 20 min to obtain a 3.33 g / L chitosan / water dispersion. Add 2 mmol of Bi(NO3)3·5H2O and 0.1 g of citric acid and stir for 20 min to make the final bismuth salt concentration 0.033 mol / L and the citric acid concentration 1.67 g / L. Stir thoroughly to dissolve the chitosan to obtain solution A. Bismuth nitrate can release hydrogen ions (H2O) by hydrolysis in water. + ), so that the solution is acidic and promotes the dissolution of chitosan. 2mmol KCl is dissolved in 5mL deionized water to obtain solution B.
[0040] (2) Solution B was slowly added dropwise to solution A over a 5-min addition time and stirred at 30° C. for 60 min to form a precursor solution.
[0041] (3) The above solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and reacted at 160° C. for 10 h. After the reaction was completed, the solution was cooled to room temperature and centrifuged. The solid was washed twice with anhydrous ethanol and deionized water, respectively, and dried at 80° C. for 6 h to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
[0042] Example 2
[0043] The difference between this embodiment and embodiment 1 is that the amount of chitosan is adjusted to 0.15 g, while other conditions remain unchanged.
[0044] Example 3
[0045] The difference between this embodiment and embodiment 1 is that the amount of chitosan is adjusted to 0.25 g, while other conditions remain unchanged.
[0046] Example 4
[0047] In this example, the amount of chitosan added in Example 1 was reduced to 0.1 g, while other conditions remained unchanged.
[0048] Example 5
[0049] In this example, the amount of chitosan added was increased to 0.3 g in Example 1, while other conditions remained unchanged.
[0050] Comparative Example 1
[0051] This comparative example is to remove chitosan from the scheme of Example 1 and only retain citric acid as a structure inducer. The preparation method is as follows:
[0052] (1) Add 2 mmol of Bi(NO3)3·5H2O and 0.1 g of citric acid to 60 mL of water to obtain a first solution. Dissolve 2 mmol of KCl in 5 mL of deionized water to obtain a second solution. Slowly add the second solution dropwise to the first solution over a 5 min addition time and stir at 30°C for 60 min to form a precursor solution.
[0053] (2) The above solution was transferred to a 100 mL polytetrafluoroethylene-lined autoclave and reacted at 160° C. for 10 h. After the reaction was completed, the solution was cooled to room temperature and centrifuged. The solid was washed twice with anhydrous ethanol and deionized water, respectively, and dried at 80° C. for 6 h to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
[0054] The products prepared in Examples 1 and 4-5 and Comparative Example 1 were subjected to X-ray diffraction, and the test results are as follows: Figure 1As shown in the figure. It can be seen that the obtained catalyst XRD curves are basically consistent with the PDF standard card of tetragonal BiOCl, and no other impurity peaks appear, which indicates that the product is BiOCl with good crystallinity. Taking BiOCl as an example, the peaks at 2θ=12.0°, 24.2°, 25.9°, 32.6°, 33.6°, 34.8°, 36.6, 46.7°, and 58.7° correspond to the (001), (002), (011), (110), (012), (111), (003), (020), and (122) diffraction peaks of tetragonal BiOCl (JCPDS#73-2060). In view of the fact that the characteristic peaks of the (110) and (001) crystal planes of BiOCl semiconductor materials are extremely important for their photocatalytic activity, the two crystal planes of BiOCl photocatalysts are compared to further explore the influence of chitosan in the synthesis process. As can be seen from the figure, with the increase of the amount of chitosan used in the preparation of BiOCl photocatalyst, the intensity of the (001) and (110) peaks of the product also increases. When the amount of chitosan added is 0.2 g, the product (denoted as BiOCl-CS 0.2 ) peaks (001), (011), (110), (012), etc., especially the (110) peak intensity reaches the maximum. However, when the chitosan addition amount is 0.1g or 0.3g, the product (respectively denoted as BiOCl-CS 0.1 、BiOCl-CS 0.3 ) decreased and the peak width increased, indicating that the size of the catalyst crystals along the corresponding crystal plane direction has become smaller. Therefore, adding an appropriate amount of chitosan in the process of preparing BiOCl photocatalyst can change the crystal growth direction of bismuth oxychloride (as shown in Examples 1 and 4-5), preferably, 1 mol of bismuth salt corresponds to adding 50-150g of chitosan as a structural inducer, and most preferably, 1 mol of bismuth salt corresponds to using 100g of chitosan as a structural inducer; if 1 mol of bismuth salt uses less than 50g or more than 150g of chitosan as a structural inducer, the photocatalytic activity of the product may be reduced compared to the photocatalytic activity of the product with 1 mol of chitosan added in the range of 50-150g.
[0055] Furthermore, the microstructures of the products of Example 1 and Comparative Example 1 were observed using an electron microscope. Figure 2As shown. Wherein, (a) is the SEM image of BiOCl of Comparative Example 1, and the product is in the form of stacked nanosheets, and the thickness of each BiOCl nanosheet is about 40-60nm. (b) is the SEM of the product of Example 1, and it is observed that the thickness of the BiOCl nanosheet is significantly reduced, about 10-35nm. In addition, it is not difficult to see from Figure (b) that the products of Comparative Example 1 and Example 1 are both disorderly stacked BiOCl nanosheets. The product of Example 1 further reduces the thickness of the BiOCl nanosheet on the basis of Comparative Example 1, and most of the nanosheets are cross-stacked or stacked at a vertical angle. The product as a whole is in the form of a loose and disorderly stacked ultra-thin nanosheet. After the nanosheets are thinned, the stacking structure of the product becomes looser, and this structure is conducive to increasing the exposure rate of the active sites of the nanosheets.
[0056] like Figure 3 As shown, the chitosan (CS), the product BiOCl of Comparative Example 1 and the product BiOCl-CS of Example 1 were characterized by infrared spectroscopy. 0.2 The functional group structure of the sample was studied. It can be clearly seen from the figure that in the infrared spectrum of chitosan, the -1 The characteristic absorption peak at 1597cm corresponds to the OH stretching vibration absorption peak generated by the hydroxyl group (-OH); -1 The peak at 1381cm is the NH stretching vibration absorption peak caused by amino group (-NH2); -1 The absorption peak at 1080cm is caused by the vibration of carbon-carbon (CC) bond; -1 The absorption peak at is derived from the stretching vibration of the carbon-oxygen (CO) bond. 0.2 At 3441cm -1 and 1618cm -1 There are relatively broad absorption peaks at 529cm, which are attributed to the OH stretching vibration and HOH bending vibration occurring on the surface of water molecules. -1 The absorption peak is the adsorption of Bi-O metal bond in BiOCl, which is almost the same as the product BiOCl in Comparative Example 1. The above results also show that the chitosan in BiOCl-CS0.2 is decomposed during the preparation process.
[0057] The photocatalyst BiOCl prepared in Example 1 and Comparative Example 1 was subjected to UV-visible diffuse reflection test, and the following results were obtained: Figure 4 The UV-visible diffuse reflectance spectra are shown in Figure 2. Among them, Figure (a) is the UV-visible diffuse reflectance spectra of BiOCl and BiOCl-CS 0.2 The UV-visible diffuse reflectance spectrum of the product BiOCl in Comparative Example 1 is about 374 nm; the product BiOCl-CS in Example 1 is about 374 nm. 0.2The light absorption boundary of BiOCl in Comparative Example 1 is about 389nm. Compared with Comparative Example 1, the preparation method of Example 1 broadens the light absorption range of BiOCl photocatalyst. In addition, the band gap energy is a decisive factor affecting the photocatalytic performance. The band gap of the sample calculated by the Kubelka-Munk equation is shown in (b). The band gap energy of BiOCl, the product of Comparative Example 1, is 3.13eV, while that of BiOCl-CS, the product of Example 1, is 2.6eV. 0.2 The band gap of the product of Example 1 is about 2.95 eV, and the band gap of the product of Example 1 is 0.18 eV smaller than that of the product of Comparative Example 1. This shows that in the process of preparing BIOCl, using an appropriate amount of chitosan as a structural inducer can make BiOCl-CS 0.2 The surface chemical environment of the photocatalyst changes, and the lower band gap energy enables it to be excited by most visible light. The lower band gap energy can effectively separate the photogenerated holes and electrons generated by strong oxidation on the surface of the photocatalyst, and then quickly transfer them to the surface to participate in free radical redox reactions, showing a higher catalytic specific activity.
[0058] Photoluminescence spectroscopy (PL spectroscopy) is used to test the photogenerated carrier recombination process of the photocatalyst after receiving photons. The diffraction intensity of the characteristic peak of photoluminescence is related to the electron / hole recombination rate. A higher PL diffraction peak intensity means a high electron / hole recombination rate and fewer photogenerated electrons and holes participate in the photocatalytic reaction, and the photocatalytic performance is low at this time. Conversely, a lower PL intensity shows a high photocatalytic activity. Using an excitation light wavelength of 310nm, the fluorescence emission spectra of the photocatalysts prepared in Example 1 and Comparative Example 1 were measured as follows Figure 5 As shown in the figure, the product BiOCl-CS 0.2 The fluorescence emission intensity of BiOCl is weaker than that of BiOCl. 0.2 It can reduce the recombination rate of photogenerated electron pairs and has higher photocatalytic performance.
[0059] like Figure 6 As shown, the product BiOCl of Comparative Example 1 and the product BiOCl-CS of Example 1 were tested by nitrogen adsorption experiment. 0.2 The specific surface area of both samples is 400 nm. Both samples show a type IV isotherm with an H3 hysteresis loop, which is a typical characteristic isotherm of mesoporous samples. 0.2 The specific surface areas are 9.5464 cm 2 / g and 25.0871cm 2 / g. It can be seen that the product BiOCl-CS in Example 1 0.2The specific surface area of the BiOCl product of Example 1 is 2.63 times that of the BiOCl product of Example 1. The above results show that the method for preparing the BiOCl photocatalyst of the present invention uses an appropriate amount of low molecular weight chitosan as an inducer during the preparation process, which helps to increase the specific surface area and adsorption capacity of the material. The increased specific surface area is conducive to providing more active sites for photocatalysis and improving the specific activity of the catalyst, while the increased adsorption capacity can improve the adsorption of organic pollutants in wastewater, thereby improving the photocatalytic degradation efficiency.
[0060] Comparative Example 2
[0061] This comparative example is to prepare BiOCl hollow microsphere photocatalyst according to the operation method of Example 1 in Chinese patent application CN110813325A mentioned in the background technology, wherein the molecular weight of chitosan is 8000, and 0.5g of chitosan is dispersed in 5mL of mixed acid solution. Take 1.5g of bismuth nitrate and dissolve it in 5mL of mixed acid solution. Take 0.2g of potassium chloride and dissolve it in 5mL of mixed acid solution. Among them, the mixed acid solution is a mixed solution obtained by mixing formic acid and acetic acid with a volume concentration of 10wt% in a volume ratio of 1:1.
[0062] Mix chitosan solution and bismuth nitrate solution in a volume ratio of 1:1, add the chitosan solution dropwise into the bismuth nitrate solution, and stir at 5°C for 100 min to make it into a colloidal state (such as Figure 7 Chitosan in the beaker shown is in a colloidal state); a 2% potassium chloride solution of the chitosan solution volume is slowly added to the system under stirring conditions, and stirred at a constant temperature of 5°C for 100 minutes; the reaction system is then transferred to a high-pressure reactor, and homogeneously reacted at a temperature of 50°C and a rotation rate of 3rpm / min for 24 hours, and then centrifuged to obtain a product; the product is washed with distilled water 3 times and dried at 50°C overnight to obtain a BiOCl hollow microsphere photocatalyst (the microscopic morphology at 2μm scale is shown in FIG. Figure 8 shown).
[0063] Photocatalytic performance test
[0064] The photocatalysts of Examples 1-5 and Comparative Examples 1-2 were used in tetracycline degradation experiments. 100 mL of a tetracycline (TC) solution with an initial concentration of 10 mg / L was measured and placed in a beaker, and 0.05 g of each catalyst sample was weighed and added to the beaker. The water temperature was maintained at 20°C, and stirred in a dark environment for 30 minutes. After reaching adsorption-desorption equilibrium, a sample was taken as a blank control. Then, the light source (300W xenon lamp) was turned on, and a sample was taken every 10 minutes. After filtering twice with a 0.22 μm water filter membrane, the absorbance of TC was measured with a UV-visible spectrophotometer, and the degradation rate was calculated. Fig. 9As shown, the degradation effects of different groups of photocatalysts on tetracycline under visible light irradiation are better than those of comparative example 1; although the photocatalyst of comparative example 2 has a better photocatalytic degradation effect on tetracycline than comparative example 1, it is still inferior to the BiOCl photocatalysts of examples 1-5 of the present invention. Among them, the degradation rate of tetracycline by the product of example 1 reaches 88.36% in 60 minutes; while under the same conditions, the degradation rate of tetracycline by the product of comparative example 2 reaches 65% in 60 minutes. Fig. 9 The photocatalytic degradation experiment shows that the disordered stacked BiOCl photocatalyst prepared by using low molecular weight chitosan and citric acid as a dual structure inducer has a higher catalytic efficiency than the BiOCl hollow microsphere photocatalyst of Comparative Example 2.
[0065] In summary, the loosely disordered ultrathin nanosheet BiOCl photocatalyst prepared by the present invention has good light absorption ability and low recombination rate of photogenerated electron pairs, and has good application prospects in degrading refractory organic pollutants in wastewater.
[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. These modifications or replacements, or the technical features in the above embodiments may be combined in the manner described in the embodiments if they do not conflict with each other, and these modifications, replacements or combinations do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a disorderly stacked ultrathin nanosheet BiOCl photocatalyst, characterized in that: The steps include: S1, dispersing chitosan with a molecular weight of 1000-4000Da into water, stirring to obtain a 1.6-5.0g / L chitosan aqueous dispersion, adding a water-soluble bismuth salt and citric acid thereto, wherein the final concentration of the bismuth salt is 0.03-0.05mol / L, and the final concentration of the citric acid is 1.5-2.0g / L, stirring to fully dissolve the chitosan, and obtaining a first solution; S2, providing a chloride salt aqueous solution with a concentration of 0.3-0.5 mol / L, wherein the molar amount of bismuth salt in the first solution and the molar amount of chloride ions in the chloride salt aqueous solution are 1:1-1.2, and the chloride salt aqueous solution is uniformly added to the first solution over a period of 5-10 min, and stirred to form a precursor solution; S3, transferring the precursor solution into a high pressure reactor and sealing it, and reacting it at 150-170°C for 6-12 hours; S4. After the reaction is completed, the mixture is cooled to room temperature and centrifuged. The solid is washed with ethanol and deionized water and dried to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
2. The preparation method according to claim 1, characterized in that: In S1, the molecular weight of chitosan is 2000-3000 Da; and 50-150 g of chitosan is used for every 1 mol of bismuth salt.
3. The preparation method according to claim 2, characterized in that: In S1, the concentration of chitosan / water dispersion was 3.33 g / L; the final concentration of bismuth salt was 0.033 mol / L, and the final concentration of citric acid was 1.67 g / L.
4. The preparation method according to claim 1, characterized in that: In S1, the water-soluble bismuth salt is at least one of bismuth nitrate, bismuth acetate, bismuth citrate and any one of the aforementioned bismuth salt hydrates.
5. The preparation method according to claim 1, characterized in that: In S2, the chloride salt refers to one of potassium chloride, sodium chloride and hexadecyl ammonium chloride; preferably potassium chloride.
6. The preparation method according to claim 1, characterized in that: The operating temperature in S1 and S2 is 25-50°C, preferably 30-35°C.
7. The preparation method according to claim 1, characterized in that: In S3, the reaction is stopped at 160° C. for 10-12 hours, and then the reaction is completed.
8. The preparation method according to claim 1, characterized in that: In S4, after the reaction is completed, the mixture is cooled to room temperature and centrifuged. The solid is washed with ethanol and deionized water for more than two times, and kept at 50°C-80°C for 6-10 hours to obtain a disorderly stacked ultrathin nanosheet BiOCl photocatalyst.
9. A disorderly stacked ultrathin nanosheet BiOCl photocatalyst, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. The disorderly stacked ultrathin nanosheet BiOCl photocatalyst according to claim 9, characterized in that: The thickness of the BiOCl nanosheet in the nanosheet BiOCl photocatalyst is 15-35 nm, the band gap energy is 2.95 eV, the light absorption edge is 389 nm, and the BET surface area is 25.0871 cm 2 / g.
Citation Information
Patent Citations
Preparation method of BiOCl hollow microsphere photocatalyst
CN110813325A